Therapy Effect of Ethanol Extract of Binahong Tuber on Superoxide Dismutase (SOD) of Kidney of Rat Induced by Alloxan - Ummah, Silviana Maslakhatul; Hasanah, Hafidatul (ALCHEMY, 2015)
Binahong (Anredera cordifolia (Ten.)Steenis) tuber is one of the plant that is not utilized yet for medicine. The aims of this research are to extract Binahong tuber Â and determine superoxide dismutase (SOD) activity of kidney of rat (RattusNorvegicus) induced by Aloxsan. Extraction of binahong tuber was conducted by maceration method using 70% ethanol. The ethanol extract was used for therapy of Rat induced by Aloxsan and to determine SOD activity. Measuring of SOD kidney activity was conducted on 6 group of rat are D1 (control), D2 (0,5 % CMC-Na, dose 1 mL/200 g body weight), D3 (aloxsan 32 mg/200g body weight), D4, D5, D6 (aloxan 32 mg/kg body weight with therapy. Doses of extract binahong tuber were 25, 50 and 75 mg/kg body weight, respectively.The results showed that therap y of 70 % ethanol extract of Binahong tuber could increase the SOD activity of rat kidneys. But, after analyzed by ANAVA one way, the therapy did not give a real effect with value of Î±0,05 (0,1290,05). Duncan test showed that there was significant difference between D3 and D4. So the effective dose was 25 mg/kg body weight. Phytochemical test showed that ethanol extract of binahong tuber contained alkaloid, flavonoid, saponin, tanin and terpenoid.Â Keywords: Tuber of Anredera cordifolia (Ten.) Steenis, Superoxide Dismutase, Alloxan